2022
DOI: 10.1136/bmjsrh-2022-201579
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation, effectiveness, and safety of immediate postpartum intrauterine device insertion: a systematic literature review

Abstract: BackgroundIntrauterine devices (IUDs) are highly effective contraception. IUDs inserted directly following delivery provide immediate birth control and may decrease unintended pregnancies, including short-interval pregnancies, thereby mitigating health risks and associated economic burden.MethodsThis systematic literature review included published global data on the utilisation, effectiveness, and safety of postpartum intrauterine devices (PPIUDs) of any type. English language articles indexed in MEDLINE, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…IUCD is the method of choice in post partum period. 16 Birth spacing of a minimum of two years has improved fetal and maternal health. [17][18][19] and thus a method should be used after delivery that is effective and has lesser failure rates to achieve adequate birth spacing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IUCD is the method of choice in post partum period. 16 Birth spacing of a minimum of two years has improved fetal and maternal health. [17][18][19] and thus a method should be used after delivery that is effective and has lesser failure rates to achieve adequate birth spacing.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Post-partum IUCD insertion is effective and safe but underutilized method of contraception. 16 A study has showed lesser menorrhagia in post-partum IUCD insertion 14 and in another study 15 it was 4% i.e. equal in both groups.…”
Section: Introductionmentioning
confidence: 93%
“…It is also cost-effective and readily available, with a short learning curve for service providers to learn its insertion technique [16][17][18][19] Despite the promising results elicited by the FIGO endeavor and government enthusiasm and support in the participating six countries, PPIUCD remains an under-utilized contraceptive option and falls short of expectations in lowering fertility rates in those populations, where it is most needed. A recent systemic review on the utilization of PPIUCD globally comes to the conclusion that despite its safety and efficacy it remains an underused contraceptive option [20]. It concludes with the observation that future research is warranted and vital to explore the reasons behind these discouraging trends and the low acceptance and provision of PPIUCDs currently.…”
Section: Status Of Ppiucd As a Viable Popular Contraceptive Optionmentioning
confidence: 99%
“…The intrauterine device (IUD) is a safe and highly effective form of reversible contraception, and IUD use is increasing globally 1. The paper published in this edition is a credible and comprehensive review of early postpartum IUD (PPIUD) experiences 2. In summary, the authors show that PPIUDs decrease unintended pregnancy rates and short-interval pregnancies, lessen economic burden, and are safe for most people seeking contraception.…”
mentioning
confidence: 99%